The importance of trade for developing countries - BALASSA, B. (PSL Quarterly Review, 2013)
Participation in international trade provides a variety of benefits to developing countries. This paper provides an empirical and policy analysis of the principal issues involved. The author reviews past trends in developing country exports, before presenting evidence on exports and on economic growth following alternative development strategies. The effects of trade orientation on economic performance are then evaluated and the future prospects for developing country exports are analysed. JEL: F10, F43